Possibilities for resource sharing among public libraries in Metro Manila - Yabes, Janette G.
This paper intends to ascertain the possibilities of resource sharing among public libraries in Metro Manila. It attempts to find out the existing resources and facilities available in these libraries and to determine if these libraries are willing to participate in any resource sharing activities; to determine the type of resource sharing activities these libraries are willing to engage in and to determine the possible benefits these libraries will acquire from the proposed resource sharing arrangement.
The four public libraries located in Metro Manila constitute the respondents of the study. Data were gathered thru a questionnaire composed of two parts: the general information and the library cooperation.
The questionnaire were given personally to the concerned professionals and the responses were analyzed and tabulated. The result showed that most of the respondents are presently engaged in resource sharing activities. These are indexing of periodicals, inter-library access, reference assistance and staff training.
With regards to library cooperation, all of the respondents indicated that they are willing to engage in cooperative cataloging, union catalog and staff training. Moreover, the possible benefits that they could acquire from the proposed resource sharing arrangement are for the strength of resources, collection development and professional development.
Typescript.
Vita.
Undergraduate Thesis (B.L.S.)--University of the Philippines, Diliman
Keywords: Library cooperation -- Philippines -- Manila Metropolitan Area; Public libraries -- Philippines -- Manila Metropolitan Area